A Geochemical Model of Fluids and Mineral Interactions for Deep Hydrocarbon Reservoirs - Jun Li; Raheel Ahmed; Qian Zhang; Yongfan Guo; Xiaochun Li (Geofluids)
A mutual solubility model for CO2-CH4-brine systems is constructed in this work as a fundamental research for applications of deep hydrocarbon exploration and production. The model is validated to be accurate for wide ranges of temperature (0–250°C), pressure (1–1500 bar), and salinity (NaCl molality from 0 to more than 6 mole/KgW). Combining this model with PHREEQC functionalities, CO2-CH4-brine-carbonate-sulfate equilibrium is calculated. From the calculations, we conclude that, for CO2-CH4-brine-carbonate systems, at deeper positions, magnesium is more likely to be dissolved in aqueous phase and calcite can be more stable than dolomite and, for CO2-CH4-brine-sulfate systems, with a presence of CH4, sulfate ions are likely to be reduced to S2− and H2S in gas phase could be released after S2− saturated in the solution. The hydrocarbon “souring” process could be reproduced from geochemical calculations in this work.